Caracterização hidrogeológica do aquífero cauê, quadrilátero ferrífero, MG: Subsídios para a gestão dos recursos hídricos no quadrilátero ferrífero - Maria Antonieta Alcantara Mourao (2007)
The Cauê aquifer encompasses the geological unit that is the host of the Iron Quadrangle bodies of iron ore (Cauê formation). It has got significant hydrogeological potential, which is used for part of the water supply for Belo Horizontes metropolitan area, and has got a fundamental importance for the maintenance of the general environmental conditions of the region. In the areas involved in mineral extraction activities, the aquifer is affected by the dewatering procedures activities which are necessary for the expansion of the mining site. Considering the necessity of a deep and wide knowledge regarding the aquifer, in order to properly manage the water resources in an area of great geologic/hydrogeologic complexity, a research method with a multidisciplinary approach was systematically planned and carried out. It was verified that the groundwater flow and storage are limited to the three greatregional blocks: Serra do Curral Homoclinal; Moeda Sinclinal; and, Tamanduá-Mutuca Transpressive Shear Zone. Intense compartmenting can be seen as a result of faulting and the presence of basic dikes and less permeable rocks. Groundwater flow occurs along the layers,due to the dissolution and the differential lixiviation of the mineral, and also on the discontinuity planes of the rocks, which are represented by fractures, cleavages and faultings. Evidences were found, pointing out that the recent (neotectonic) reactivation has generated preferential drainage surfaces. Physical tests, made in laboratories, showed that the highest values of hydraulic conductivity (maximum of 2.3x10-5 m/s) and total porosity (maximum of 46.3%) are associated to medium hematites (semi-friable), laminated compact hematites and decomposed itabirites. The hydraulic conductivity is distinctively higher in the directions thatare approximately parallel to the bedding. The groundwater recharge estimated for the area, using five different methods and employing information of distinct natures, revealed a mean value of 30.3% of the annual average precipitation, with a minimum of 2.2% and a maximumof 47.0%. There is a strong correlation between the distinct types of soils and geology, with the recharge values, with the higher rates being observed in the domains of Cauê formation (above 38%). The groundwater residence time within the Cauê aquifer generally corresponds to values between 50 and 300 years. The 18O and 2H contents indicate quick infiltration. As to their chemical characteristics, the waters of the Cauê aquifer are very poorly mineralised (average electric conductivity of 13.2 S/cm), having no specific signature. Thetop limiting geo-hydrostratigraphic unit of the Cauê aquifer, named the Gandarela aquifer, is made of carbonatic rocks and displays important karst features where it joins with the Serra da Moeda Sinclinal, and in the oriental segment of the Serra do Curral Homoclinal.Its hydraulic connexion with the Cauê aquifer was not conclusively determined, taking into account the chemical and isotopic aspects, as well as the field relations. It exhibits a chemical identity characterised by high hydraulic conductivity (mean of 108.0 S/cm), 13C enrichment (around 10.0), and a composition in which, calcium, magnesium and bicarbonatespredominate. The groundwater discharges, on the Moeda Sinclinal, show residence times from 170 up to more than 500 years, and the mineral concentrations, progressively higher from the North to the South, indicating groundwater flows oriented from the Jardim Canadáplateau. The confining hydrostratigraphic unit, named Batatal, constitutes the base for the Cauê aquifer and displays low permeability in almost all of its domain, a fact that is indicated by the piezometric relations in the surroundings of the mines located in the region, and by the positioning of the majority of the groundwater discharge points exactly at the contact of the Cauê with the Batatal unit. In the Tamanduá-Mutuca tectonic shear zone, the great density of structures (especially ruptile ones), due to the deformation, favoured the percolation of groundwater in the phyllites that show two important discharge points along the Fechos stream. The water in these two points is characterized by a reducing condition and a high concentration of dissolved metals, especially iron. Physical tests made on phyllite samples, with different degrees of weathering, indicated higher hydraulic values of conductivity (6.9x10-6 m/s) and porosity (29.1%), for the rocks that were much decomposed.